The anatomy of oblivion in José Eduardo Agualusa's A General Theory of Oblivion. Issue 1 (18th March 2022) - Adebayo, Sakiru
Abstract: José Eduardo Agualusa is one of the few novelists who write with the intention of exploring the workings of memory in their novels. In A General Theory of Oblivion, he provides a nuanced portrayal of oblivion as a mnemonic phenomenon in post-war Angola. In this paper, I trace the different strands of the politics of oblivion brought to bear in the novel. I argue that– because of the calculated silencing and mechanisms of repression observable in post-war Angola – the novel rescues the memory of the civil war from fading into oblivion. I argue that while the novel establishes oblivion as a variant of forgetting, it also invites us to consider ways in which oblivion may not be forgetting per se. That is, while forgetting may be understood simply – or simplistically – as a failure to remember, oblivion is an active, and sometimes passive, indifference to memory. I conclude that with forgetting, the past seems out of sight but with oblivion, the past is present but overlooked. Oblivion, therefore, exists within the boundaries of what is known and unknown, what is revealed and concealed. In all, this paper explores how A General Theory of Oblivion creates an anatomy of oblivion in post-war Angola and how that expands our understanding of the politics of memory in general.